Association between SEMA3A signaling pathway genes and BMD/OP risk: An epidemiological and experimental study - Zhou, Hao-long; Wei, Mu-hong; Di, Dong-sheng; Zhang, Ru-yi; Zhang, Jian-li; Yuan, Ting-ting; Liu, Qian; Zhou, Ting-ting; Huang, Qin; Wang, Qi (Frontiers in Endocrinology, 2022)
Objective: This study aimed to explore the associations of genetic variants in the semaphorin 3A (SEMA3A) signaling pathway genes, including SEMA3A, NRP1, PLXNA1, PLXNA2 and PLXNA3 with osteoporosis (OP) risk and bone mineral density (BMD) in a Chinese Han older adult population. Study design and method: A two-stage design was adopted. Total of 47.8kb regions in the 5 genes were sequenced using targeted next-generation sequencing (NGS) technology in the discovery stage, and the discovered OP-related single nucleotide polymorphisms (SNPs) were further genotyped using improved multiple linkage detection reaction technique in the validation stage. Methods of ALP/TRAP staining, real-time fluorescent quantitative PCR, and cell proliferation and apoptosis assays were performed with MC3T3-E1 and RAW 264.7 cell lines to clarify biological effects of observed functional variants in cell lines responsible for bone mass remodeling. Results: Total of 400 postmenopausal women (211 OP cases) were involved in the discovery stage, where 6 common and 4 rare genetic variants were found to be associated with OP risk. In the validation stage among another 859 participants (417 women, 270 OP cases), the PLXNA2 rs2274446 T allele was associated with reduced OP risk and increased femoral neck (FN) BMD compared to the C allele. Moreover, significant associations of NRP1 rs2070296 with FN BMD/OP risk and of NRP1 rs180868035 with lumbar spine and FN BMDs were also observed in the combination dataset analysis. Compared to the osteoblasts/osteoclasts transfected with the wild-type NRP1 rs180868035, those transfected with the mutant-type had reduced mRNA expression of osteoblastic genes (i.e., ALP, RUNX2, SP7 and OCN), while elevated mRNA expression of osteoclastic genes (i.e., TRAP, NFATc1 and CTSK). Furthermore, mutant NRP1 rs180868035 transfection inhibited osteoblast proliferation and osteoclast apoptosis, while promoted osteoclast proliferation and osteoblast apoptosis in corresponding cell lines. Conclusion: Genetic variants located in NRP1 and PLXNA2 genes were associated with OP risk and BMD. The NRP1 rs180868035 affects bone metabolism by influencing osteoblasts and osteoclasts differentiation, proliferation and apoptosis.